First find of biogenic activity in the Palaeoproterozoic of the Singhbhum craton (E India) - van Loon, A.J.; Mazumder, R. (Geologos, 2013)
The Palaeoproterozoic succession of the Singhbhum craton in E. India was hitherto considered as almost entirely siliciclastic and partly volcanogenic. Here we describe, from the fine-grained, tidally influenced shale facies of the Palaeoproterozoic Chaibasa Formation (2.1-1.6 Ga), a fine, originally more or less horizontal, wavy to strongly undulating (later locally deformed) lamination. Investigation of these laminae shows that they must be ascribed to the accumulation of fine particles on microbial mats that covered a sandy substrate. The structures must therefore be considered as stromatolites, features that are accepted as proof of the presence of micro-organisms, in this case most probably cyanobacteria. The interpretation of biogenic activity is supported by microscopic analysis. It is the first description of traces left by biogenic activity that took place in the Palaeoproterozoic of the Singhbhum craton.